Primer on the In-home Teleneurologic Examination: A COVID-19 Pandemic Imperative. Issue 2 (April 2021) - Boes, Christopher J.; Leep Hunderfund, Andrea N.; Martinez-Thompson, Jennifer M.; Kumar, Neeraj; Savica, Rodolfo; Cutsforth-Gregory, Jeremy K.; Jones, Lyell K.
Abstract : It is imperative in the coronavirus disease 2019 (COVID-19) pandemic that we serve our patients by implementing teleneurology visits for those who require neurologic advice but do not need to be seen face to face. The authors propose a thorough, practical, in-home, teleneurologic examination that can be completed without the assistance of an on-the-scene medical professional and can be tailored to the clinical question. We hope to assist trainees and practicing neurologists doing patient video visits for the first time during the COVID-19 pandemic, focusing on what can, rather than what cannot, be easily examined.